Terracotta art in northern India - Srivastava, S. K. (Surendra Kumar), 1928- (Delhi : Parimal Publications, 1996)
Study with special reference to Uttar Pradesh, India.
Includes bibliographical references (p. [283]-287).
Keywords: Terra-cotta figurines, Indic -- India -- Uttar Pradesh; Pottery, Ancient -- India -- Uttar Pradesh; 18-91